2004
DOI: 10.1161/01.res.0000122041.73808.b5
|View full text |Cite
|
Sign up to set email alerts
|

Collateral Artery Growth (Arteriogenesis) After Experimental Arterial Occlusion Is Impaired in Mice Lacking CC-Chemokine Receptor-2

Abstract: Abstract-Arteriogenesis has been associated with the presence of monocytes/macrophages within the collateral vessel wall. Induced macrophage migration in vivo is driven by the binding of monocyte chemoattractant protein-1 (MCP-1, or CCL2 in the new nomenclature) to the CCR2-chemokine receptor on macrophages. To determine whether the CCL2-CCR2 signaling pathway is involved in the accumulation of macrophages in growing collateral vessels, we used mice that are deficient in CCR2 in a model of experimental arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
173
4
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(190 citation statements)
references
References 48 publications
12
173
4
1
Order By: Relevance
“…The proangiogenic activity of MCP-1 is well documented but is dependent on a functional CCR2 receptor, and despite significantly elevated thrombus MCP-1 in the CCR2 Ϫ/Ϫ mice, impaired neovascularization was observed (13,21). Others have found that CCR2 Ϫ/Ϫ mice have impaired neovascular responses in various models of disease (12,24). Although specific proangiogenic mediators were not evaluated at days 12 and 21 because of difficulty in clean separation of vein wall and thrombus, we speculate that reduced bFGF in CCR2 Ϫ/Ϫ mice at 8 days (but not VEGF) may have contributed to this impaired later neovascular response.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The proangiogenic activity of MCP-1 is well documented but is dependent on a functional CCR2 receptor, and despite significantly elevated thrombus MCP-1 in the CCR2 Ϫ/Ϫ mice, impaired neovascularization was observed (13,21). Others have found that CCR2 Ϫ/Ϫ mice have impaired neovascular responses in various models of disease (12,24). Although specific proangiogenic mediators were not evaluated at days 12 and 21 because of difficulty in clean separation of vein wall and thrombus, we speculate that reduced bFGF in CCR2 Ϫ/Ϫ mice at 8 days (but not VEGF) may have contributed to this impaired later neovascular response.…”
Section: Discussionmentioning
confidence: 75%
“…Pleotropic angiogenic growth factors released by polymorphonuclear neutrophils (PMNs) and monocytes are known to be present in the resolving thrombus and include vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF) (21)(22)(23). The pathobiology of angiogenesis also involves CCR2 signaling (13,24,25). Fibrinolysis of venous thrombi is thought to be primarily mediated by urokinase plasminogen activator (uPA) from monocytic cells (26), as evidenced from impaired venous thrombus resolution in mice lacking uPA but not tissue-type plasminogen activator (27).…”
Section: Eep Vein Thrombosis (Dvt)mentioning
confidence: 99%
“…CCL2, in particular, was critically involved in infarct-associated inflammation and subsequent healing in a mouse model of myocardial infarction, but its absence did not influence angiogenesis (76). CCL2 has, however, been implicated in ischaemia-induced arteriogenesis in a murine hind-limb ischaemia model (77), and may therefore be relevant in similar collateralization in the context of chronically ischaemic myocardium.…”
Section: Chemokine-induced Angiogenesis In Inflammatory and Fibroprolmentioning
confidence: 99%
“…51 In addition, average capillary blood velocity is higher in rats that have undergone exercise training. 3 Thus, using empirical relationships for viscosity and hematocrit distribution, 25,46 and experimental measurements of blood oxygenation and velocity in ligated rat EDL 3,16,17,44,46 we simulated blood flow for perfused tissue and partially perfused tissue (where only half of the tissue arterioles have blood flow).…”
Section: Blood Flowmentioning
confidence: 99%
“…The blood oxygen saturation in the inlet arterioles (SO 2A ) plummets following ligation, and slowly recovers to the healthy value of 0.6-0.8 over 2 weeks. 23,64 Based on measurements of tissue PO 2 and hemoglobin saturation calculations 16,17,44 we estimate SO 2A to be 0.06, 0.3, and 0.6 at 2, 7, and 14 days following ligation, respectively.…”
Section: Tissue Oxygenationmentioning
confidence: 99%